2006
DOI: 10.1007/s00268-005-0416-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the Lichtenstein Operation of Strangulated Groin Hernia a Safe Procedure?

Abstract: The use of monofilament polypropylene mesh for strangulated inguinal hernia repair is safe, and the risk of the local infectious complications is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 77 publications
1
27
0
7
Order By: Relevance
“…In Group 1, 51.7% (58) of the patients had hernias on the right side, while 48.3% (54) had hernias on the left side. In Group 2, 61.5% (24) of the patients had hernias on the right side, and 38.5% (15) had their hernias on the left side. There were no statistically significant differences between the two groups with respect to gender, hernia type, or hernia localization (p>0.05) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Group 1, 51.7% (58) of the patients had hernias on the right side, while 48.3% (54) had hernias on the left side. In Group 2, 61.5% (24) of the patients had hernias on the right side, and 38.5% (15) had their hernias on the left side. There were no statistically significant differences between the two groups with respect to gender, hernia type, or hernia localization (p>0.05) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Wysocki et al (15) previously performed a study of 77 patients who underwent the Lichtenstein procedure. In this study, two of the patients had seromas, while two patients had limited wound infections.…”
Section: Wound Infection-recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that polypropylene meshes can be used safely in inguinal hernia cases that undergo intestinal resection. [28] Polypropylene meshes are resistant against infections due to their macroporous structure and can be used safely in AWH defects. Repair techniques performed using Prolene mesh in anterior AWHs in the hands of experienced surgeons and in accordance with the technique would provide lower morbidity and recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Setelah integritas mekanik usus hilang, maka bakteri dapat menginvasi submukosa serta memasuki sirkulasi sistemik melalui vena porta dan sistem limfatik. [4][5][6][7] Beberapa substansi bakteri dapat ditemukan dari cairan peritoneum dan jaringan limfatik, bahkan bila tidak terjadi perforasi. 4 Pada keadaan obstruksi dan strangulasi usus, kadar laktat darah merupakan salah satu indikator kimiawi darah yang dapat diukur.…”
Section: Pendahuluanunclassified